Improving site flow through supervisory routines : Developing process guidelines for supervisors in surface treatment services - Aunio, Perttu (My University, 2026)
The objective of this thesis is to improve supervisory routines of a target company that provides surface treatment services to increase workflow efficiency. The starting point is the observation that work site interruptions increase costs and undermine project profitability. Supervisors play a key role in managing the site flow, but their methods are inconsistent and often based on longterm experience in the field, which makes it difficult to train new supervisors. The central research question is: How can standardized supervision routines improve workflow, productivity, financial results, and customer satisfaction in surface treatment services? The study was conducted in accordance with the Design Science Research Methodology (DSRM) approach, which aims to solve practical problems through the development of an artifact. The research process progressed from problem definition to solution design and development as well as to the demonstration and evaluation of the developed artifact. The empirical data was collected from the author’s own observations and experiences, as well as from employee and customer satisfaction surveys at the case company. Additionally, the artifact was developed in collaboration with other key personnel at the company. A key outcome of the study is a set of process guidelines for supervisors, in which the supervisor’s tasks and routines are divided into different phases based on when they must be performed. The guidelines include defined tasks for pre-execution preparation, planning, work execution control and supervision, completion and post-execution activities, as well as the reporting methods associated with these tasks. In addition, a key component is the foreman’s calendar planning part, which supports the practical application of the process chart. The evaluation of the artefact was conducted as a subjective assessment by the author, in which the developed guidelines were compared to the objectives set at the beginning of the study, and their application was demonstrated in the context of a single project. The output has not yet been applied in a real-world work environment, and its effects have not been empirically validated in practical implementation. Consequently, the presented results are limited to a conceptual examination and a single demonstration. This study offers a practical contribution by presenting a structured model for developing supervision practices in a service-oriented construction site environment. In the future, it is recommended to test the model in practical projects and systematically collect feedback on its use, for example through interviews, so that the functionality and effectiveness of the guidelines can be assessed more reliably in various operational environments.

Tämän opinnäytetyön tavoitteena on parantaa pintakäsittelypalveluja tarjoavan kohdeyrityksen työnjohtajarutiineja työnkulun tehostamiseksi. Lähtökohtana on havainto, että työmaan keskey-tykset lisäävät kustannuksia ja heikentävät projektien kannattavuutta. Työnjohtajilla on keskeinen rooli työmaan virtauksen hallinnassa, mutta heidän toimintatapansa ovat vaihtelevia ja perustuvat usein pitkäaikaiseen kokemukseen alalta, mikä vaikeuttaa uusien työnjohtajien kouluttamista. Keskeinen tutkimuskysymys on: Miten standardoidut työnjohtorutiinit voivat parantaa työnkulkua, tuottavuutta, kannattavuutta ja asiakastyytyväisyyttä pintakäsittelypalveluissa? Tutkimus toteutettiin Design Science Research Methodology (DSRM) -lähestymistavan mukaisesti, jonka tavoitteena on ratkaista käytännön ongelmia kehittämällä artefakti. Tutkimusprosessi eteni ongelman määrittelystä ratkaisun suunnitteluun ja kehittämiseen sekä kehitettyjen artefaktien esittelyyn ja arviointiin. Empiiriset tiedot kerättiin tekijän omien havaintojen ja kokemusten perus-teella sekä kohdeyrityksessä toteutettujen työntekijä- ja asiakastyytyväisyyskyselyjen avulla. Li-säksi artefakti kehitettiin yhteistyössä yrityksen muiden avainhenkilöiden kanssa. Tutkimuksen keskeisenä tuloksena on työnjohtajille tarkoitettu prosessiohjeisto, jossa työnjohtajan tehtävät ja rutiinit on jaoteltu eri vaiheisiin sen mukaan, milloin ne on suoritettava. Ohjeisiin sisäl-tyy määriteltyjä tehtäviä ennakkovalmisteluun, suunnitteluun, työn aikaiseen ohjaukseen ja val-vontaan, valmistumiseen ja jälkitoimiin sekä näihin tehtäviin liittyvät raportointimenetelmät. Li-säksi keskeinen osa on työnjohtajan kalenterisuunnitteluosa, joka tukee prosessikaavion käytän-nön soveltamista. Artefaktin arviointi toteutettiin kirjoittajan subjektiivisena arviointina, jossa kehitettyjä ohjeita verrattiin tutkimuksen alussa asetettuihin tavoitteisiin ja niiden soveltamista havainnollistettiin yhden projektin yhteydessä. Tulosta ei ole vielä sovellettu todellisessa työympäristössä, eikä sen vaikutuksia ole empiirisesti vahvistettu käytännön toteutuksessa. Näin ollen esitetyt tulokset ra-joittuvat käsitteelliseen tarkasteluun ja yhteen esimerkkiin. Tämä tutkimus tarjoaa käytännönläheisen panoksen esittelemällä jäsennellyn mallin valvontakäy-täntöjen kehittämiseksi palvelulähtöisessä rakennustyömaaympäristössä. Tulevaisuudessa on suositeltavaa testata mallia käytännön projekteissa ja kerätä järjestelmällisesti palautetta sen käytöstä, esimerkiksi haastattelujen avulla, jotta ohjeiden toimivuutta ja tehokkuutta voidaan arvi-oida luotettavammin erilaisissa toimintaympäristöissä.
Keywords: customer satisfaction; project management; renovation building (activity); supervision of work; processes; quality management; Industrial Systems Analytics; Master's Programme in Industrial Systems Analytics